Assessment of anxiety markers in schoolchildren in a distance learning environment - Askarbek Kussainov; Mekhirnissa Khavaydarova; Zhuparkul Beissenova; Zhuldyz Kongyrova (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study outlines the theoretical foundations of diagnosing and dealing with children’s anxiety in a school setting. Based on these observations, the study proposes and tests practical anxiety management techniques. The study introduces a new term - school isolation anxiety - which is given an original definition. A total of 1,892 secondary school students (grades 4 to 9) in various regions of the Republic of Kazakhstan participated in the study. The sample encompasses 60 classes divided equally into 30 experimental groups and 30 control groups. Preliminary observation and interviews with participants allowed to identify 10 markers of school isolation anxiety, enabling its diagnosis. The next phase of the study suggested the development of anxiety management techniques. The use of the identified anxiety markers and the parallel application of techniques resulted in a significant reduction of anxiety levels in the experimental groups.